Total body bone mineral density and various spinal disorders: a Mendelian randomization study - Jiang, Qingyu; Gao, Haihao; Shi, Xudong; Wu, Yan; Ni, Wentao; Shang, Aijia (Frontiers in Endocrinology, 2023)
Observational studies have yielded inconsistent findings regarding the correlation between bone mineral density (BMD) and various spinal disorders. To explore the relationship between total-body BMD and various spinal disorders further, we conducted a Mendelian randomization analysis to assess this association. Methods: Two-sample bidirectional Mendelian randomization (MR) analysis was employed to investigate the association between total-body BMD and various spinal disorders. The inverse-variance weighted (IVW) method was used as the primary effect estimate, and additional methods, including weighted median, MR-Egger, simple mode, and weighted mode, were used to assess the reliability of the results. To examine the robustness of the data further, we conducted a sensitivity analysis using alternative bone-density databases, validating the outcome data. Results: MR revealed a significant positive association between total-body BMD and the prevalence of spondylosis and spinal stenosis. When total-body BMD was considered as the exposure factor, the analysis demonstrated an increased risk of spinal stenosis (IVW odds ratio [OR] 1.23; 95% confidence interval [CI], 1.14-1.32; P < 0.001) and spondylosis (IVW: OR 1.24; 95%CI, 1.16-1.33; P < 0.001). Similarly, when focusing solely on heel BMD as the exposure factor, we found a positive correlation with the development of both spinal stenosis (IVW OR 1.13, 95%CI, 1.05-1.21; P < 0.001) and spondylosis (IVW OR 1.10, 95%CI, 1.03-1.18; P = 0.0048). However, no significant associations were found between total-body BMD and other spinal disorders, including spinal instability, spondylolisthesis/spondylolysis, and scoliosis (P > 0.05). Conclusion: This study verified an association of total-body BMD with spinal stenosis and with spondylosis. Our results imply that when an increasing trend in BMD is detected during patient examinations and if the 2 This is a provisional file, not the final typeset article patient complains of numbness and pain, the potential occurrence of conditions such as spondylosis or spinal stenosis should be investigated and treated appropriately.